Safety training impediments that exist for Company XYZ English as a second language employees - Feliciano, MaryAnn (University of Wisconsin-Stout, 2019)
The purpose of this study was to identify the potential safety training impediments that exist for Company XYZ's ESL workers. The first goal of this study consisted of evaluating Company XYZ's training and testing materials for language that meets the needs of non-English speakers, both in communicating and assessing content. The second goal was to assess Company XYZ's safety training surveying methods used to determine ESL workers' ability to identify hazards associated with their work processes. The researcher utilized scholarly articles, government agency databases, and established industry recognized standards to identify pertinent background knowledge on each goal. Two focus group sessions were conducted at Company XYZ to gather the management and employees' perceptions of the organization's safety training program. The researcher identified safety training impediments with the training materials being written/presented in English-only for ESL workers at Company XYZ. Based on the hazard assessment portion ESL workers had lower pre-test scores when the training was performed in English opposed to utilizing the translanguaging approach during the post-test. The researcher recommends that Company XYZ use the translanguaging approach for training its ESL population and work with an outside organization to provide free alternative based English courses for ESL employees.
Keywords: Safety education; English language--Study and teaching--Foreign speakers--Health risk assessment; Risk assessment